Simple Python-Based Application for Transforming Apparent Resistivity Data from Schlumberger Configuration to Wenner Configuration Using the Linear Filter Method - Kareth, Zakaria Victor; Bowaire , Anike Nelce; Haselo, Linus (Universitas Cenderawasih, 2024)
Research has been conducted regarding the design of a simple Python-based application to transform apparent resistivity values ​​from the Schlumberger configuration into apparent resistivity values ​​from the Wenner configuration using the linear filter method. The application developed was then validated using field data measurements from two different locations, namely Nendali Village in the East Sentani district and Buper Waena in the Heram Jayapura district. At each measurement point, two Vertical Electrical Sounding (VES) measurements were performed using Schlumberger and Wenner configurations. The apparent resistivity values ​​from the Schlumberger configuration were transformed using the application created, and the results were compared with observational data from the Wenner configuration. Field data were taken for as many as six samples per logarithmic cycle, with the Schlumberger AB/2 configuration electrode spacing equal to the Wenner configuration electrode spacing. The maximum stretch lengths in Nendali and Buper villages were 26 m and 40 m, respectively. The research results show a match between the apparent resistivity values ​​of the Wenner configuration obtained from field observations and the transformation results. This suitability was demonstrated qualitatively through the similarity of the apparent resistivity curve trend between the transformed and field observation data. Quantitatively, this suitability is shown by the slope value of the comparison curve of field observation data and transformed data, which in Nendali and Buper Villages is 0.75 and 0.98, respectively. The conclusion of this study is that a simple application that has been designed and created can be used to transform apparent resistivity values ​​from the Schlumberger configuration to the Wenner configuration. A comparison between the transformed data and field observation data shows that suitability is highly dependent on the quality of the field data.